From Lyrics To Listening: A Creative Program To Improve The Listening Skills Of Grade 9 Students At Nurul Jadid Junior High School Through English Songs - Leni Wulandari; Umi Nur Faizah; Galuh Rofanda; Khoiratul Ummah; Wardatul Karomah; Mochlis Ekowijayanto; Nur Aini (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
Listening is widely recognized as one of the most challenging skills for junior high school EFL learners, especially when instruction still depends on monotonous, textbook-based audio materials that offer limited authenticity. The From Lyrics to Listening program was designed as a creative instructional model to enhance the listening proficiency of ninth-grade students at Nurul Jadid Junior High School through the integration of English songs. This study employed a descriptive qualitative approach complemented by simple quantitative comparisons to examine students’ progress before and after the intervention. During a four-week implementation period, students engaged in structured pre-listening, while-listening, and post-listening activities supported by digital platforms such as YouTube and LyricsTraining. The results indicate a notable improvement in students’ listening comprehension, particularly in their ability to recognize vocabulary, interpret lyrical meaning, and understand the main ideas of spoken texts. Classroom observations further showed increased enthusiasm, active participation, and learner confidence. Overall, the findings highlight that incorporating English songs into listening instruction is both enjoyable and pedagogically effective, contributing to enhanced motivation and improved listening outcomes.